PERANAN PENDIDIKAN KEPENDUDUKAN TERHADAP PELESTARIAN LINGKUNGAN HIDUP - Azizah Husin (Program Studi Kependudukan, Pascasarjana Universitas Sriwijaya, 2013)
make population have knowledge, attitude, and skill about environmental. The environmental problems nowdays are getting worse. The demage has been happening on earth such as air pollution, the land, and the air. Goal is to make population has good vision, and then awareness, so they make friendly relationship with environment. Population are not treating environment an object of need of human only, but ethical manner.